Thermo- and electro-dual responsive poly(ionic liquid) electrolyte based smart windows. Issue 10 (5th January 2017) - Chen, Fei; Ren, Yongyuan; Guo, Jiangna; Yan, Feng
Abstract : A thermo- and electro-dual responsive poly(ionic liquid) electrolyte based smart window system shows both tunable transparency and electrochromic properties. Abstract : Thermo- and electro-dual responsive poly(ionic liquid) (PIL) based electrolytes were synthesized by co-polymerization of N -isopropylacrylamide (NIPAM) with (or without) 3-butyl-1-vinyl-imidazolium bromide ([BVIm][Br]) using diallyl-viologen (DAV) as both the cross-linking agent and electrochromic material.